2019
DOI: 10.1590/1678-4685-gmb-2018-0173
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the critical region 5p15.3–p15.2 associated with cri-du-chat syndrome

Abstract: Cri-du-chat syndrome (CdCs) is one of the most common contiguous gene syndromes, with an incidence of 1:15,000 to 1:50,000 live births. To better understand the etiology of CdCs at the molecular level, we investigated theprotein–protein interaction (PPI) network within the critical chromosomal region 5p15.3–p15.2 associated with CdCs using systemsbiology. Data were extracted from cytogenomic findings from patients with CdCs. Based on clinical findings, molecular characterization of chromosomal rearrangements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 82 publications
(98 reference statements)
0
20
0
2
Order By: Relevance
“…MRPL3 is one of the recently discovered hub genes associated with acute mountain sickness, which may be used as a biomarker and therapeutic target for an accurate diagnosis and treatment in the future [ 7 ]. MRPL36 is significantly associated with the meow syndrome by analyzing the protein interaction network [ 36 ]. Moreover, MRPs can have a positive effect on the treatment of diseases.…”
Section: Mrps Associated With Diseases Except Cancersmentioning
confidence: 99%
“…MRPL3 is one of the recently discovered hub genes associated with acute mountain sickness, which may be used as a biomarker and therapeutic target for an accurate diagnosis and treatment in the future [ 7 ]. MRPL36 is significantly associated with the meow syndrome by analyzing the protein interaction network [ 36 ]. Moreover, MRPs can have a positive effect on the treatment of diseases.…”
Section: Mrps Associated With Diseases Except Cancersmentioning
confidence: 99%
“…Cri-du-chat syndrome is a congenital syndrome associated with deletion of part of the short arm of chromosome 5 [10][11][12]. Deletions can vary in size from extremely small to the entire short arm.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, it is estimated that there are around 500-700 patients (Rodríguez-Caballero et al, 2012, and unpublished data from patient's Associations). It has been suggested that the great phenotypic variability observed among individuals with this syndrome is related to both the size and the location of the deletion (between 5p15.3 and 5p15.2 bands), since it is a chromosomal region with a large gene content (Nguyen et al, 2015;Correa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%